2012
DOI: 10.5005/jp-journals-10024-1122
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of COX2 Expression between Oral Squamous Cell Carcinoma, Leukoplakia and Normal Mucosa

Abstract: Aim:To compare cyclooxygenase 2 expression (COX2-E) between normal, oral leukoplakia lesions and different grades of oral squamous cell carcinoma (SCC). Materials and methods:Around 90 paraffin embedded blocks consisting of 45 SCC, 15 leukoplakia and 17 controls were selected for immunohistochemistry (IHC) for detection of COX2-E. COX2-E was divided in four grades, as A (0-10%), B (11-40%), C (41-70%) and D (> 70%) cellularity.Results: Mean age of the patients was 55.17 ± 18.41

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 19 publications
3
8
0
Order By: Relevance
“…[17] The results reported in this study about the grades of malignancy, are agreed with studies that found no correlation between the expression of COX-2 and the grade of malignancy. In the study performed by Pandey et al [30] and Amirchaghmaghi et al [2] no significant difference was observed in COX-2 expression between different grades of OSCC, these findings confirmed the results of present study. Itoh et al also found no association between COX-2 expression and histological grades of tumor.…”
Section: Discussionsupporting
confidence: 96%
See 3 more Smart Citations
“…[17] The results reported in this study about the grades of malignancy, are agreed with studies that found no correlation between the expression of COX-2 and the grade of malignancy. In the study performed by Pandey et al [30] and Amirchaghmaghi et al [2] no significant difference was observed in COX-2 expression between different grades of OSCC, these findings confirmed the results of present study. Itoh et al also found no association between COX-2 expression and histological grades of tumor.…”
Section: Discussionsupporting
confidence: 96%
“…[14] This finding is in consistent with the results of the present study. Similar findings have been reported by Chan et al [18] for head and neck SCC and by Amirchaghmaghi et al [2] and Nagatsuka et al [31] about OSCC.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This speculation is consistent with the previous finding that demonstrated an increase in epithelial apoptosis in the ulcerative/erosive type of OLP 31 . Interestingly, COX-2 was also weakly expressed in the suprabasal cell layers of normal oral epithelium (Figure 1), which is in line with the findings from other studies in normal oral epithelium32, 33 and in normal epidermis 34 …”
Section: Discussionsupporting
confidence: 93%